Poster 100 Adherence to the recommendations in respiratory rehabilitation of the British Thoracic Society in Patients with cystic fibrosis: a study of Colombian Physiotherapists (2014)
Main Outcome Measures: This self-report questionnaire was (79.4%). Interventions with high level of evidence (Grade A) suchas: Bronchial Hygiene Therapy (54.0%) and Active Cycle of Breathing Techniques (35.3%) were identified. However, high percentage of physiotherapists practiced interventions with lower grade of recommendation (Grade D) such as: hypertonic saline and bronchodilator to prevent bronchospasm (33.9%), and using manual therapy techniques and thoracic mobility exercises (38.4%) to correct postural and breathing problems. Conclusions: In conclusion we confirm important differences in therapeutic assistant components of the respiratory rehabilitation raised by the British Thoracic Society for patients with cystic fibrosis. used to identify interventions and components of respiratory rehabilitation programs as recommended by the British Thoracic Society (from 1 for “always applied” to 5 for “never applied”). Demographic and practice data were collected. Results or Clinical Course: The sample included 224 physiotherapists, from which 169 were women (75.4%) and 55 were men (24.5%). Most of the sample age ranged from 20 to 29 years old